2005
DOI: 10.1029/2004wr003705
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical modeling of the spatial variability of arsenic in groundwater of southeast Michigan

Abstract: [1] During the last decade one has witnessed an increasing interest in assessing health risks caused by exposure to contaminants present in the soil, air, and water. A key component of any exposure study is a reliable model for the space-time distribution of pollutants. This paper compares the performances of multi-Gaussian and indicator kriging for modeling probabilistically the spatial distribution of arsenic concentrations in groundwater of southeast Michigan, accounting for arsenic data collected at privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(117 citation statements)
references
References 21 publications
2
112
0
3
Order By: Relevance
“…We assessed model validity using an independent validation dataset of 371 private wells. The spatial models include those commonly applied to predict arsenic: a geostatistical model, a nearest neighbor approach, and arithmetic averages in US Public Lands Survey-defined townships and sections (Bates et al, 2004;Chen et al, 1995;Chen et al, 2003;Chen et al, 2004;Goovaerts et al, 2005;Hassan et al, 2003;Serre et al, 2003;Steinmaus et al, 2003). These models were built on a rich dataset of 6050 arsenic measurements collected over a tenyear period in southeastern Michigan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We assessed model validity using an independent validation dataset of 371 private wells. The spatial models include those commonly applied to predict arsenic: a geostatistical model, a nearest neighbor approach, and arithmetic averages in US Public Lands Survey-defined townships and sections (Bates et al, 2004;Chen et al, 1995;Chen et al, 2003;Chen et al, 2004;Goovaerts et al, 2005;Hassan et al, 2003;Serre et al, 2003;Steinmaus et al, 2003). These models were built on a rich dataset of 6050 arsenic measurements collected over a tenyear period in southeastern Michigan.…”
Section: Discussionmentioning
confidence: 99%
“…Geostatistical Model-The development of the geostatistical model is described in detail elsewhere (Goovaerts et al 2005). Briefly, the geostatistical model capitalizes on the spatial correlation between arsenic values to make predictions at unsampled locations.…”
Section: Models For Predicting Arsenic Concentrations In Private Wellmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of spatial correlation in hydrochemical variables is an important tool in the analysis of groundwater chemistry. This paper investigates the spatial correlation of the Mathura ground water data sets using Kriging method (Franco et al, 2009;Goovaerts, 1997 andGoovaerts et al, 2005). Spatial assessment of groundwater chemistry is important for revealing the correlation between location and the hydrochemical variables in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Examples are given of the type of semivariogram found in the study area, while Kriged maps illustrate the spatial relationships found. The semivariogram analysis of the geo-statistical assessment revealed that for the dataset, the spatial correlation has a relatively short range therefore the sill value is difficult to analyze because of a spatial trend in the data, leading to an increase of the semi-variance almost immediately after the sill has been reached (Goovaerts, 1997 andGoovaerts et al, 2005). Thirteen water samples were collected from phreatic aquifer in clean pre-rinsed100 ml plastic (polyethylene) bottles.…”
Section: Methodsmentioning
confidence: 99%